Organizing Democracy through General Elections in Indonesia: The Challenge of Law Enforcement and State Stability - Ridwan Arifin; Saktiani Nurul Hidayat (Sospol : Jurnal Sosial Politik, 2019)
One of the developments in Indonesia's political democracy is marked by the existence of legal framework that state sovereignty belongs to the people and is carried out in accordance with the 1945 Constitution. On the basis of the formulation of leadership succession in the executive and legislative branches it is mandated by Article 22 E paragraph (2). However, in practice the constitutional arrangement in Law Number 42 of 2008 concerning the General Election of the President and Vice President shows that it is inconsistent with statements in the constitution. As stipulated in Article 3 paragraph (5) states that the election of the President and Vice President is held after the election of the DPR, DPD and DPRD. At the end of the Constitutional Court through Decree No. 14/PUU-XI/2013 states that the selection of models is unconstitutional. Based on this assessment the constitutionality of the norm selection method is based on the simultaneous interpretation of the constitution both from the initial intentions and historical interpretations. The simultaneous constitutional electoral plan was called born as an effort to shift the direction of the transition to democracy in a strengthening system so that democratic consolidation of direct democratic practices tends to be transactional, corrupt, manipulative, high cost and to preserve power can be minimized in the practice of constitutional democratic dimensions to understand and sovereign.